2013
DOI: 10.1007/s10661-013-3086-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of power plant emission reductions on a nearby wilderness area: a case study in northwestern Colorado

Abstract: This study evaluates the effect of emission reductions at two coal-fired power plants in northwestern Colorado on a nearby wilderness area. Control equipment was installed at both plants during [1999][2000][2001][2002][2003][2004] to reduce SO 2 and NOx emissions. One challenge was separating the effects of local from regional emissions, which also declined during the study period. The long-term datasets examined confirm that emission reductions had a beneficial effect on air and water quality in the wildernes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(35 reference statements)
2
2
0
Order By: Relevance
“…Despite this complicating factor, lake concentration patterns were very similar to those of total inorganic N concentrations at high-elevation NADP sites (Figure B), supporting the conclusion that deposition is an important influence on nitrate export. This result is consistent with recent studies in eastern North America and Europe where declines in watershed N export appear to be have occurred in response to reductions in N deposition over the past decade. ,, We previously reported that streamwater sulfate in high-elevation watersheds has responded rapidly to reductions in sulfate deposition, , and herein we show the response to N deposition may be similar at least in areas with high rates of deposition where surface water nitrate concentrations are elevated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite this complicating factor, lake concentration patterns were very similar to those of total inorganic N concentrations at high-elevation NADP sites (Figure B), supporting the conclusion that deposition is an important influence on nitrate export. This result is consistent with recent studies in eastern North America and Europe where declines in watershed N export appear to be have occurred in response to reductions in N deposition over the past decade. ,, We previously reported that streamwater sulfate in high-elevation watersheds has responded rapidly to reductions in sulfate deposition, , and herein we show the response to N deposition may be similar at least in areas with high rates of deposition where surface water nitrate concentrations are elevated.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with recent studies in eastern North America and Europe where declines in watershed N export appear to be have occurred in response to reductions in N deposition over the past decade. 15,16,18 We previously reported that streamwater sulfate in high-elevation watersheds has responded rapidly to reductions in sulfate deposition, 39,40 and herein we show the response to N deposition may be similar at least in areas with high rates of deposition where surface water nitrate concentrations are elevated.…”
Section: ■ Discussionsupporting
confidence: 70%
“…Recent studies have shown O & G emissions of non-methane hydrocarbons (NMHC) such as short-chain alkanes (C 1 -C 4 ) and alkenes act as precursors to ozone (Pétron et al, 2012(Pétron et al, , 2014Edwards et al, 2013;Gilman et al, 2013;Karion et al, 2013), but the potential for these emissions to contribute to primary and secondary OA in the region has not been investigated. Additionally, agricultural practices and powerplant operations in the greater Colorado region contribute to visibility impairment and ecosystem degradation through formation of secondary nitrate and sulfate-containing compounds (Williams and Tonnessen, 2000;Nanus et al, 2003;Blett et al, 2004;Burns, 2004;Boy et al, 2008;Malm et al, 2013;Mast and Ely, 2013; T. M. Thompson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown O & G emissions of non-methane hydrocarbons (NMHC) such as short-chain alkanes (C 1 -C 4 ) and alkenes act as precursors to ozone (Pétron et al, 2012(Pétron et al, , 2014Edwards et al, 2013;Gilman et al, 2013;Karion et al, 2013), but the potential for these emissions to contribute to primary and secondary OA in the region has not been investigated. Additionally, agricultural practices and powerplant operations in the greater Colorado region contribute to visibility impairment and ecosystem degradation through formation of secondary nitrate and sulfate-containing compounds (Williams and Tonnessen, 2000;Nanus et al, 2003;Blett et al, 2004;Burns, 2004;Boy et al, 2008;Malm et al, 2013;Mast and Ely, 2013; T. M. Thompson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%